Efeito dos herbicidas Facet®, Primoleo® e Roundup® isolados e em mistura sobre índices de condição corporal e o sistema antioxidante de girinos de Rhinella ictérica - Reichert, Leici Maria Machado (2021)
Brazil is one of the world's largest consumers of pesticides, whose massive use affects ecosystems and non-target organisms. Amphibians have suffered population declines due to habitat degradation, disease, and exposure to pollutants such as pesticides. Tadpoles are particularly affected by residues that reach the aquatic environment and there are several biomarkers related to the oxidative balance in these animals that can be quantified. The species Rhinella icterica (Bufonidae) is native to regions of Atlantic forest in southern and southeastern Brazil and its aquatic phase occurs in areas close to rice fields, in which the herbicides atrazine, glyphosate and quinclorac are used. The present study aimed to verify the effect of the formulations Facet®, Primoleo® and Roundup® on the biochemical composition and oxidative balance of Rhinella icterica tadpoles. The concentrations were chosen based on those found in environments impacted by agriculture.Two laboratory cultivations were performed in the laboratory with tadpoles collected in non-contaminated areas and exposed to different concentrations of commercial formulation of the herbicides Primoleo® (active ingredient atrazine), Facet® (active principle quinclorac) and Roundup® (active principle glyphosate). In one of the tests, three concentrations of each pesticide (10, 20 and 40 μg / L of Primoleo® and Facet®; and 100, 250 and 500 μg / L of Roundup®) were used and quantified the levels of superoxide dismutase (SOD) and catalase (CAT) activity; levels of oxidative damage markers, TBARS (thiobarbituric acid reactive substances) and carbonylated proteins; in addition, body condition markers were determined. There were no significant variations in the oxidative stress markers assessed. The absence of mortality in these concentrations shows a sublethal condition. In the other experimental trial, the animals were exposed to isolated herbicides (20 μg / L atrazine: 250 μg / L glyphosate, and 20 μg / L quinclorac) or their mixtures. The same markers were quantified, plus GST activity. There was variation in the levels of antioxidant enzymes and other markers, especially the increase in SOD, GST and TBARS levels in animals exposed to atrazine in isolation, and an increase in CAT in the group exposed to the mixture of the three herbicides. Both tests suggest a more toxic potential for atrazine. The results indicate that even ecologically relevant concentrations of these herbicides, as well as their mixtures, can cause biochemical changes in amphibians, which may be related to physiological and tissue changes that may in the longer term compromise the survival of these animals.